Handbook of constructive mathematics - Bridges, D. S. 1945-; Ishihara, Hajime; Rathjen, Michael; Schwichtenberg, Helmut 1942- (Cambridge University Press, 2023)
This handbook gives a complete overview of modern constructive mathematics - mathematics in which 'there exists' always means 'we can construct' - and its applications. Written and edited by leading experts, it is an indispensable reference for established constructive mathematicians and guide to the field for graduate students and other newcomers.